Theory U : leading from the future as it emerges : the social technology of presencing - Scharmer, Claus Otto, 1961- (Berrett-Koehler Publishers, Inc., 2016)
Access the deepest source of inspiration and vision We live in a time of massive institutional failure that manifests in the form of three major divides: the ecological, the social, and the spiritual. Addressing these challenges requires a new consciousness and collective leadership capacity. In this groundbreaking book, Otto Scharmer invites us to see the world in new ways and in so doing discover a revolutionary approach to learning and leadership. In most large systems today, we collectively create results that no one wants. What keeps us stuck in such patterns of the past? It's our blind spot, that is, our lack of awareness of the inner place from which our attention and intention originate. By moving through Scharmer's U process, we consciously access the blind spot and learn to connect to our authentic Self--the deepest source of knowledge and inspiration. Theory U offers a rich diversity of compelling stories, examples, exercises, and practices that allow leaders, organizations, and larger systems to cosense and coshape the future that is wanting to emerge. This second edition features a new preface in which Scharmer identifies five transformational trends and describes U process case stories around the world. There are also eight color drawings by Kelvy Bird that capture U journey applications and illustrate the concepts in the book, as well as new resources for applying the principles and practices.